PI/NCC carbon membrane : effect of heating rates towards oxygen separation performance - Norazlianie, Sazali; R., Mamat; W. N. W., Salleh; A. F., Ismail; F., Aziz; N. I., Mahyon (IOP Publishing, 2020)
Separation of oxygen and nitrogen gas was considered by utilizing tubular carbon membrane (TCMs) arranged from polymeric precursors. A coating methodology called dip coating strategy was utilized to manufacture the TCMs utilizing P84 co-polyimide and Nanocrystalline cellulose (NCC) as the primary precursor and added additives individually. Past examination has demonstrated that properties of PI/NCC can be adjusted by changing the carbonization parameter i.e. time, temperature and condition. The statement of PI/NCC on the tubular supported help was utilized to deliver an assortment of TCMs for gas separation by basic carbonization process. In this examination, the heating rates was controlled to watch the impact of TCMs on gas permeation by setting the heat rates at 1, 3, 5, and 7 °C/min. It was demonstrating that the gas separation performance was profoundly influenced by the carbonization heating rates amid the manufacture of PI/NCC-based carbon membrane. Likewise, heat rates at (3 °C/min) demonstrates an enhancement in the membrane selectivity and separation performance.